2022
DOI: 10.1007/s12306-022-00769-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for nerve injury following shoulder dislocation

Abstract: Background The glenohumeral joint dislocation can be associated with major nerve injury. The reported prevalence and risk factors for major nerve injury are variable and this injury can have a severe and life-long impact on the patient. The objectives of this study were to analyse the prevalence of major nerve injury following shoulder dislocation and examine risk factors. Management and outcomes of nerve injury were explored. Methods A 1 year retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 16 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…No additional studies meeting the inclusion criteria were found upon reviewing the references of the included articles. In total, 13 studies were included in the systematic review [ 5 , 7 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No additional studies meeting the inclusion criteria were found upon reviewing the references of the included articles. In total, 13 studies were included in the systematic review [ 5 , 7 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…These dislocations can cause damage to the soft tissues surrounding the joint, including the rotator cuff tendons, nerves in the area, labrum, and humeral or glenoid bone lesion [ 3 , 4 ]. However, there is limited evidence regarding this association following nerve injury [ 5 , 6 , 7 ]. The close relationship between the glenohumeral joint and the brachial plexus makes nerve injury a potential complication of shoulder dislocation, with the axillary nerve being the most frequently affected nerve [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Axillary nerve injury is also a well-recognized complication of glenohumeral dislocations, with about 3% incidence and rising with age, time to reduction, and associated fracture 3 . Many spontaneously recover given time, but for those with high-grade nerve injury and deltoid dysfunction, it is a devastating complication with prolonged disability [3][4][5] . These pathologies in isolation have reliable treatment algorithms, but together they prove challenging to treat without clear consensus for surgical intervention.…”
mentioning
confidence: 99%